Strategy for Instilling Islamic Education Values on Migrant Family Students: A Case Study of SDN Ponjanan Timur 2 - Wildan Humaidi; Muliatul Maghfiroh (al-Afkar, Journal For Islamic Studies, 2025)
The instillation of Islamic educational values ​​is an important thing that must be applied to students, but its application to students of SDN Ponjanan Timur 2 is still relatively low due to the lack of supervision from parents who are immigrant workers so that strategies and materials for Islamic educational values ​​are needed to overcome this. The purpose of this study is to determine the strategy and material for instilling Islamic educational values ​​in students from migrant families. This study uses a qualitative method of the case study approach, data sources are obtained from interviews, observations and documentation, where the informants of this study are teachers, students and families of students. The results of the study show: first, the strategy for instilling Islamic educational values ​​in students from migrant families is carried out using the strategy of using lecture methods, discussions, demonstrations, habits, role models, advice, and punishment. Second, some materials for instilling Islamic educational values ​​in students from migrant families applied by the school are materials on faith, worship and morals.